The Importance of Understanding the Stages of COVID-19 in Treatment and Trials - Griffin, Daniel O.; Brennan-Rieder, Denise; Ngo, Binh; Kory, Pierre; Confalonieri, Marco; Shapiro, Leland; Iglesias, Jose; Dube, Michael; Nanda, Neha; In, Gino K.; Arkfeld, Daniel; Chaudhary, Preet; et al. (AIDS reviews, 2021)
COVID-19, caused by SARS-CoV-2, continues to be a major health problem since its first description in Wuhan, China, in December 2019. Multiple drugs have been tried to date in the treatment of COVID-19. Critical to treatment of COVID-19 and advancing therapeutics is an appreciation of the multiple stages of this disease and the importance of timing for investigation and use of various agents. We considered articles related to COVID-19 indexed on PubMed published January 1, 2020-November 15, 2020, and considered papers on the medRxiv preprint server. We identified relevant stages of COVID-19 including three periods: pre-exposure, incubation, and detectable viral replication; and five phases: the viral symptom phase, the early inflammatory phase, the secondary infection phase, the multisystem inflammatory phase, and the tail phase. This common terminology should serve as a framework to guide when COVID-19 therapeutics being studied or currently in use is likely to provide benefit rather than harm.
Keywords: COVID-19; SARS-CoV-2; phases; cytokine storm; antivirals; immunotherapy; Scopus; JCR